Adaptive integral type‐terminal sliding mode control for PEMFC air supply system using time delay estimation algorithm. Issue 1 (14th October 2020) - Abbaker A. M., Omer; Wang, Haoping; Tian, Yang
Abstract: This paper proposes a new cascaded adaptive integral type‐terminal sliding mode control based on time delay estimation algorithm (cascaded‐AITSMC‐TDE) for the proton exchange membrane fuel cell (PEMFC) system with unknown uncertainties. The proposed cascaded‐AITSMC‐TDE scheme is composed of two components: time delay estimation (TDE) technique and cascaded‐adaptive integral type‐terminal sliding mode control (AITSMC). The TDE is employed to approximate unknown uncertain dynamic. The cascaded‐AITSMC is integrated with TDE to control oxygen excess ratio (stoichiometry) and air flow rate keeping a proper system performance under load disturbance, avoiding the oxygen starvation. The stability of the proposed cascaded‐AITSMC‐TDE via closed‐loop system is verified by Lyapunov approach. In order to validate the effectiveness and robustness of the proposed cascaded‐AITSMC‐TDE, a comparative study with a single loop AITSMC, cascaded integral type‐terminal sliding mode control (cascaded‐ITSMC) and cascaded integral sliding mode based‐time delay estimation (cascaded‐ISMC‐TDE) is carried out, and the corresponding simulation results exhibit that the proposed controller provides fast convergence of tracking trajectories with less fluctuations.